Feasibility study of the three-tether axisymmetric wave energy converter. (15th February 2018) - Sergiienko, N.Y.; Rafiee, A.; Cazzolato, B.S.; Ding, B.; Arjomandi, M.
Abstract: There are numerous designs and concepts that have been offered to extract energy from ocean waves. A heaving buoy is distinguished as the most popular device which predominantly harnesses energy from the vertical motion in waves. One such device is the bottom-referenced submerged heaving buoy represented by the Carnegie Clean Energy CETO system. The total power absorption of this converter can be increased by replacing the single-tether power take-off system by a three-tether mooring configuration thereby making motion controllable in heave and surge. The current paper provides a comparative performance analysis of the generic submerged heaving buoy connected to one tether and the three-tether converter in terms of the buoy motion, and design of the power take-off and mooring systems. This is accompanied by a techno-economic analysis of two converters. Highlights: The three-tether wave energy converter can absorb twice as much power as the same buoy connected to one tether. The three-tether WEC can share mooring points with adjacent devices in the array. The three-tether WEC experiences much less motion in all degrees of freedom while reducing load on the mooring system. Surge is effectively coupled to the power take-off and contributes the same amount of power as heave. The three-tether WEC can produce cheaper electricity than its single-tether counterpart.